Library Experiential Marketing Strategy as a Means of Increasing Library Satisfaction in the Use of E-Resources During the Covid-19 Pandemic - Endang Fatmawati (GoAcademica Research & Publishing, 2021)
This study aims to analyze the effects of library experiential marketing strategies on user satisfaction levels during the Covid-19 pandemic, using a quantitative approach. Data were collected through observation, questionnaires, and reviews of related literature. Based on the results obtained, experiential marketing is a suitable marketing concept for libraries. This strategy is bound to aid libraries in providing pleasant and unforgettable services. The priority of experiential marketing strategy during the Covid-19 pandemic is to observe the responses of users by testing the variables of sense, feel, think, act, and relate/linkage. These five independent variables have a positive and significant effect on user satisfaction, indicating the potential for libraries to improve user experience by connecting through real-life users. In conclusion, experiential marketing strategies can provide positive experiences for users and, consequently, improve the interest in optimizing the use of electronic information resources, even during the Covid-19 pandemic.